Impact of Financial Technology on the Financial Performance of Conventional Banks in Indonesia - Riny Jefri; Nurul Maghfirah Surianto; Wayan Krisna Eka Putra; Maya Novitasari (Universitas Pendidikan Ganesha, 2024)
This study intends to investigate variations in banking financial performance concurrent with Fintech expansion and to elucidate the influence of Fintech, or financial technology, on banking financial performance. Quantitative research is what this kind of study. For the years 2013 through 2020, conventional banking businesses listed on the Indonesia Stock Exchange (IDX) were the subject of this study. The Indonesia Stock Exchange's official website and the official websites of each firm provided research data in the form of yearly reports. Out of 43 data points, 22 firms made up the sample. Purposive sampling is the approach used for sampling. From the results of the Paired T Test Sample, the application of fintech has had an influence on the performance and health of conventional banking in Indonesia which is the sample in this research, although seen from the BOPO side it does not provide the same thing. According to the study's findings, fintech's rise is a disruptive innovation for the banking sector. This problem is closely correlated with people's need for financial convenience. Fintech has the potential to help banks with issues such as the unbanked population and increase financial penetration.